Exercise-Induced Arrhythmia or Munchausen Syndrome in a Marathon Runner? - Robert Gajda; Wojciech Drygas; Jacek Gajda; Pawel Kiper; Beat Knechtle; Magdalena Kwaśniewska; Maciej Sterliński; Elżbieta Katarzyna Biernacka (Diagnostics, 2023)
A 36-year-old professional marathon runner reported sudden irregular palpitations occurring during competitions, with heart rates (HR) up to 230 bpm recorded on a sports HR monitor (HRM) over 4 years. These episodes subsided upon the cessation of exercise. Electrocardiograms, echocardiography, and cardiac magnetic resonance imaging results were borderline for athlete’s heart. Because an electrophysiology study and standard exercise tests provoked no arrhythmia, doctors suspected Munchausen syndrome. Ultimately, an exercise test that simulated the physical effort of a competition provoked tachyarrhythmia consistent with the HRM readings. This case demonstrates the diagnostic difficulties related to exercise-induced arrhythmia and the diagnostic usefulness of sports HRMs.